2002
DOI: 10.1348/000712602162436
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit processes in a hypothesis testing task

Abstract: We present the results of two experiments investigating the factors that determine responding on the pseudo-diagnosticity task. In Expt 1 we manipulated people's beliefs about the degree to which an initial piece of evidence supported a focal hypothesis and found decreased pseudo-diagnostic (PD) responding when the evidence offered low support for the focal hypothesis. In Expt 2 we manipulated the instructions given to participants. We found that instructions to select evidence to help decide between the focal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…By contrast, Feeney, Evans, and Venn (2008) showed that simply offering anchoring statistical information about a rare feature was enough to increase the rate of row choices. Our results corroborate and extend Feeney et al's findings and therefore also contrast with Evans et al's (2002) assumption by demonstrating that, once the relevance constraint is satisfied, reasoners can engage in diagnostic reasoning comparing values associated with a unique feature across alternative hypotheses even in the absence of explicit instructions to consider the alternative option. Indeed, when D 1 was relevant, a large majority of participants chose to make row selections.…”
Section: Dual-process Theorysupporting
confidence: 89%
“…By contrast, Feeney, Evans, and Venn (2008) showed that simply offering anchoring statistical information about a rare feature was enough to increase the rate of row choices. Our results corroborate and extend Feeney et al's findings and therefore also contrast with Evans et al's (2002) assumption by demonstrating that, once the relevance constraint is satisfied, reasoners can engage in diagnostic reasoning comparing values associated with a unique feature across alternative hypotheses even in the absence of explicit instructions to consider the alternative option. Indeed, when D 1 was relevant, a large majority of participants chose to make row selections.…”
Section: Dual-process Theorysupporting
confidence: 89%
“…Broadbent (1987, 1988) demonstrated that there was a dissociation between participants' performance on a complex knowledge task and their explicit understanding of the task. Evans, Venn, and Feeney (2002) demonstrated how reasoning biases in a hypothesis-testing task can be reduced via instructions that induce participants to think of explicit alternatives rather than relying on implicit assumptions. Additionally, the dissociation between performance and expression of knowledge has been demonstrated in a natural linguistic structure task (Pacton, Perruchet, Fayol, & Cleeremans, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…When selecting evidence participants consider only the focal hypothesis (the hypothesis supported by the initial piece of evidence), neglect the alternative hypothesis, and hence select further evidence that is explicitly relevant to the focal hypothesis. Although when explicitly instructed to choose evidence to help them decide between the hypotheses, people do tend to make fewer PD choices (Evans, Venn, & Feeney, 2002), the default focus on just one hypothesis appears to be a general characteristic of human thinking (for a discussion of these issues in the context of dual process theories of thinking, see Evans, 2007).…”
mentioning
confidence: 99%